Evaluation of TP53 Variants Detected on Peripheral Blood or Saliva Testing: Discerning Germline From Somatic TP53 Variants. (3rd November 2021) - Schwartz, Alison N.; Hyman, Sophie R.; Stokes, Samantha M.; Castillo, Danielle; Tung, Nadine M.; Weitzel, Jeffrey N.; Rana, Huma Q.; Garber, Judy E.
Abstract : PURPOSE: Multigene panel testing (MGPT) identifies TP53 pathogenic or likely pathogenic (P/LP) variants in patients with diverse phenotypes, of which only one is classic Li-Fraumeni syndrome. Low variant allelic fraction (VAF) in TP53 found on germline testing may suggest aberrant clonal expansion or constitutional mosaicism. We evaluated TP53 -positive probands seen in a cancer genetics program to determine germline versus somatic status. METHODS: We reviewed TP53 -positive probands from 2012 to 2019 identified by MGPT on blood or saliva (N = 84). Available VAFs were collected. Probands with a familial variant, who met Li-Fraumeni syndrome testing criteria or who carried a founder variant, were considered germline. For those with uncertain germline status, TP53 variants were further examined using ancillary data of family members and somatic tissue. RESULTS: Of the 84 probands, 54.7% had germline variants with 33.3% meeting criteria for germline status and 21.4% confirmed through ancillary testing. Aberrant clonal expansion comprised 13.1% with clonal hematopoiesis of indeterminate potential and 2.4% with a hematologic malignancy. Constitutional mosaicism was confirmed in 8.3% probands. Definitive status could not be determined in 3.6% despite ancillary assessment, and 17.9% did not have ancillary testing. CONCLUSION: A TP53 P/LP variant found on peripheral blood or saliva MGPT does not always originate in the germline. In a clinical cancer genetics cohort, approximately half of the patients had TP53 P/LP germline variants; these patients plus those with constitutional mosaicism require intensified surveillance. A framework of multiple strategies enables discernment of germline from constitutional mosaic and acquired variants, which is essential for appropriate management.